1977
DOI: 10.1056/nejm197705192962004
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Trimester Abortion by Dilatation and Evacuation

Abstract: Abortions by dilatation and evacuation after the 12th menstrual week of pregnancy are said to be both hazardous and impractical. To evaluate this hypothesis, we compared the safety and feasibility of 6213 abortions by this means and 8662 induced by intra-amniotic instillation of saline during the 13th to the 20th week of pregnancy. Abortions by dilatation and evacuation had a lower rate for major complica-tions (0.69 vs. 1.78 per cent; P is less than 0.001) and lower rates for treatment of complications, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(42 citation statements)
references
References 11 publications
1
40
0
1
Order By: Relevance
“…[12][13][14][15][16] For second trimester abortion (13-24 weeks of gestation), medical abortion with mifepristone followed by a prostaglandin analogue is an appropriate method and has been shown to be safe and effective, according to WHO and the RCOG. [17][18][19][20][21][22] It has been well proven that pretreatment with mifepristone 24-48 hours before prostaglandin administration increases the success rate, shortens the induction-to-abortion interval and reduces the amount of prostaglandins required in the second trimester in unscarred uteri. 23,24 In our series women with previous LSCS ,mifepristone 200 mg was given 36 hours prior to the misoprostol or oxytocin and found that none of the cases had incomplete abortion or rupture probably because we had ensured improvement in Bishop's score even by putting Foley's bulb before administration of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] For second trimester abortion (13-24 weeks of gestation), medical abortion with mifepristone followed by a prostaglandin analogue is an appropriate method and has been shown to be safe and effective, according to WHO and the RCOG. [17][18][19][20][21][22] It has been well proven that pretreatment with mifepristone 24-48 hours before prostaglandin administration increases the success rate, shortens the induction-to-abortion interval and reduces the amount of prostaglandins required in the second trimester in unscarred uteri. 23,24 In our series women with previous LSCS ,mifepristone 200 mg was given 36 hours prior to the misoprostol or oxytocin and found that none of the cases had incomplete abortion or rupture probably because we had ensured improvement in Bishop's score even by putting Foley's bulb before administration of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Induction of labour by intra-amniotic instillation of saline or urea-prostaglandin F2-alpha was shown to have higher relative risks of serious complications than D&E (RR 2.6, 95% CI 1.9-3.6 and RR 1.9, 95% CI 1.2-3.1, respectively). One randomised trial comparing D&E to intra-amniotic instillation of prostaglandin F2-alpha supported these findings.…”
Section: Safety Of Dandementioning
confidence: 99%
“…A D&E refers to any instrumental evacuation of the pregnant uterus through the cervix at z13 weeks gestation. 7 This operational definition was proposed by the US Centers for Disease Control to differentiate second trimester curettage procedures from first trimester procedures (vacuum aspiration or suction curettage). Although vacuum aspiration can be performed to 16 weeks gestation using large-bore cannulae (14-16 mm in diameter), 37 by convention this would be referred to as a D&E.…”
Section: Relative Frequency Of Dande and Medical Abortionmentioning
confidence: 99%
“…Labour and delivery nurses caring for women throughout the process, not doctors, were the caregivers most burdened. 12 The shift to surgical second trimester abortion care did not begin until 1977, when David Grimes and colleagues published a pivotal study documenting the safety of D&E. 13 As D&E became increasingly accepted as a superior means of accomplishing second trimester abortion compared to labour induction, a small amount of research on provider perspectives on D&E resulted. Kaltreider et al found that some doctors who provided D&E had ''disquieting'' dreams and strong emotional reactions.…”
Section: Personal and Psychological Considerationsmentioning
confidence: 99%
“…Kaltreider et al found that some doctors who provided D&E had ''disquieting'' dreams and strong emotional reactions. 13 Hern found that D&E was ''qualitatively a different procedure -both medically and emotionallythan early abortion''. 14 Many of his staff members reported:…”
Section: Personal and Psychological Considerationsmentioning
confidence: 99%